Determinación del grado de absorción del mercurio por tratamiento de relaves de minería aurífera artesanal de la zona de parcoy con algas “gigartina chamissoi”. - Aredo Rubio, Oscar Iván (2011)
In order to investigate the influence of the ratio and contact time on the extent of absorption of mercury in Gigartina algae pellets (Chondracanthus) Chamissoi 30 mercury absorption tests with algae Gigartina prior chemical treatment is performed. For contrasting effect, additionally equal number of mercury absorption tests in Gigartina algae pellets without chemical treatment were also implemented. Levels ratio were evaluated: 10, 20 and 40 respectively. As the contact time was had levels: 1, 2, 3, 4 and 5 hours. Absorption rates in seaweed Gigartina mercury with chemical pretreatment, range between 39.98 and 95.14 percent percent respectively. As the percentage of mercury absorption Gigartina seaweed without chemical pretreatment, range between 22.48 and 75.42 percent percent respectively. After analysis of variance carried out, it is concluded that the variables analyzed, proportion: and contact time have significant effects on the extent of absorption of mercury in Gigartina algae pellets (Chondracanthus) Chamissoi. It also shows that increasing the proportion and contact time up to three hours favor the absorption of mercury in pellets alga Gigartina (Chondracanthus) Chamissoi.